2018
DOI: 10.21037/jtd.2017.09.154
|View full text |Cite
|
Sign up to set email alerts
|

Optimising drug dosing in patients receiving extracorporeal membrane oxygenation

Abstract: Optimal pharmacological management during extracorporeal membrane oxygenation (ECMO) involves more than administering drugs to reverse underlying disease. ECMO is a complex therapy that should be administered in a goal-directed manner to achieve therapeutic endpoints that allow reversal of disease and ECMO wean, minimisation of complications (treatment of complications when they do occur), early interruption of sedation and rehabilitation, maximising patient comfort and minimising risks of delirium. ECMO can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
169
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 106 publications
(157 reference statements)
1
169
0
8
Order By: Relevance
“…Venoarterial ECMO (VA-ECMO) provides support for both the heart and the lungs, while venovenous ECMO (VV-ECMO) only provides respiratory support. An increasing number of studies have shown that ECMO is associated with significant pharmacokinetic (PK) alterations, including an increased volume of distribution and reduced clearance ( 10 13 ). Studies on whether the PK of caspofungin will change in patients receiving ECMO are very limited and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Venoarterial ECMO (VA-ECMO) provides support for both the heart and the lungs, while venovenous ECMO (VV-ECMO) only provides respiratory support. An increasing number of studies have shown that ECMO is associated with significant pharmacokinetic (PK) alterations, including an increased volume of distribution and reduced clearance ( 10 13 ). Studies on whether the PK of caspofungin will change in patients receiving ECMO are very limited and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus guidelines recommend the use of sedation for patients receiving ECMO cannulation during the first 12–24 hours post‐cannulation, followed by minimal sedation thereafter to maintain patient comfort and prevent complications 1 . Optimization of sedation in these patients is crucial; however, altered drug pharmacokinetics (PK) in patients receiving ECMO may contribute to therapeutic failure of these agents 2‐5 …”
mentioning
confidence: 99%
“…Degradation of drugs may further worsen PK derangements. ECMO has also been shown to exacerbate the PK alterations of some drugs and may lead to either therapeutic failure or toxicity [7].…”
Section: Pharmacotherapy During Ecmo Supportmentioning
confidence: 99%